Multimorbidity, age-related comorbidities and mortality: association of activation, senescence and inflammation markers in HIV adults. (31st July 2018) - Duffau, Pierre; Ozanne, Alexandra; Bonnet, Fabrice; Lazaro, Estibaliz; Cazanave, Charles; Blanco, Patrick; Rivière, Etienne; Desclaux, Arnaud; Hyernard, Caroline; Gensous, Noemie; Pellegrin, I.; Wittkop, L.
Abstract : Background: The widespread introduction of combination antiretroviral therapy (cART) has increased survival of HIV-infected patients. However, the prevalence of age-related comorbidities remains higher than that of the general population, suggesting that individuals with HIV suffer from accelerated aging. Immune activation, senescence and inflammation could play an important role in this process. Methods: The CIADIS (Chronic Immune Activation anD Senescence) sub-study analyzed biomarkers of activation, differentiation and senescence of T cells in a cellular-CIADIS-weighted score, whereas biomarkers of inflammation were analyzed in a soluble CIADIS-weighted score using principal component analysis. Adjusted logistic regression and Cox proportional hazard models were used to determine the association between CIADIS-weighted scores and the presence of multimorbidity, time to occurrence of the first new age-related comorbidity and time to death, over a 3-year follow-up period. Results: Of 828 patients with an undetectable viral load, a higher cellular-CIADIS-weighted score and higher TNFRI levels were independently associated with the presence of multimorbidity (OR 1.3; 95% CI 1.0–1.6; P  = 0.02), but the soluble CIADIS-weighted score was not (OR = 1.1; 95% CI 0.9–1.3; P  = 0.33). A higher cellular CIADIS-weighted score (hazard ratio 2.2; P  < 0.01), higher levels of CD8 + activation and a lower CD4 + /CD8 + ratio were associated with a higher risk of age-related comorbidities. Only TNFRI was associated with mortality in a 3-year period. Conclusion: The cellular CIADIS-weighted score was independently associated with both multimorbidity at inclusion and the risk of new age-related comorbidity during a 3- year follow-up. TNFRI was associated a higher risk for mortality. Abstract : Supplemental Digital Content is available in the text